PRINSIP PERKEMBANGAN ANAK DALAM KANDUNGAN - ropikah amelia; halijah mikenola; muhammad mizwar pasaribu; rahul pasaribu; rahmah yasrah dalimunthe (Nunchi : Islamic Parenting Journal, 2023)
Basic principles of student learning development to facilitate the teaching and learning process. Education is an effort to create an environment for children that can stimulate the development of their potential and will bring about desired changes in their habits and attitudes. So, these students will be assisted by teachers, parents and other adults to utilize the capacity and potential they carry in achieving the growth and development they desire. In achieving student development maturity, it turns out that there are many principles that exist in the development process. This principle must be understood by every teacher or leader in education so that there is formation/maturation of the development experienced by students and makes it easier for educators or educational leaders to create a curriculum or educational program that will suit the students.